Stainless steel for fuel cell separator and its manufacturing method
By incorporating microscopic protrusions on the fuel cell separator surface, the contact resistance is reduced, improving fuel cell performance through increased contact area and avoiding costly coatings.
Patent Information
- Application Number
- JP2024536328
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-20
- Filing Date
- 2022-12-14
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The contact resistance between the fuel cell separator and the Gas Diffusion Layer (GDL) is high due to the small contact area and the presence of a non-conductive oxide layer, which affects the performance of the fuel cell.
The surface of the fuel cell separator is engineered with microscopic protrusions between 10 and 100 nm to increase the actual contact area, using stainless steel with specific compositions and manufacturing processes like bright annealing and chemical or mechanical surface treatments.
The increased contact area reduces the contact resistance to 10 mΩ·cm², enhancing the performance of the fuel cell without requiring expensive coating processes.
Smart Images

Figure 2025500082000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a stainless steel for a separator for a fuel cell and a manufacturing method thereof, and more particularly to a stainless steel for a separator for a fuel cell that can ensure low contact resistance by controlling the surface shape of the separator to increase the contact area with a GDL (Gas Diffusion Layer). [Background technology]
[0002] Generally, a fuel cell stack is a stack of cells each consisting of a membrane electrode assembly (MEA) including an electrolyte, electrodes, and a GDL, and a separator. Therefore, the separator is in contact with the GDL, and the contact resistance caused at the separator / GDL interface reduces the performance of the cell and the fuel cell.
[0003] The contact resistance of such a separator plate is mainly influenced by two factors. First, there is the passivation film, which is an oxide layer on the surface of the metal separator plate. The passivation film is a method that can ensure high corrosion resistance, but from the perspective of contact resistance, it is preferable to have a thickness as thin as possible because it is a non-conductive oxide layer. Secondly, it is the contact area between the separator plate and the GDL that affects the contact resistance. Since the separator plate and the GDL are objects with different surface roughness, the actual contact area between the two objects in contact has a large effect on the contact resistance. If the contact area between the separator plate and the GDL is large, the contact resistance tends to be low, and if the contact area is small, the contact resistance tends to be high, so the effect of reducing the contact resistance varies depending on how the surface shape of the separator plate is changed.
[0004] Generally, a fuel cell stack is a stack of cells, each of which is made up of a membrane electrode assembly (MEA) containing an electrolyte, electrodes, and a GDL, and a separator. The separator is in contact with the GDL, and the resistance at the separator / GDL interface is called contact resistance, which determines the performance of the cell and the fuel cell.
[0005] The contact resistance of such a separator plate is mainly influenced by two factors. The first is the passivation film, which is an oxide layer formed on the surface of the metal separator plate. The passivation film is a method that can ensure high corrosion resistance, but in terms of contact resistance, it is preferable to have as thin a thickness as possible because it is a non-conductive oxide layer. The second is the contact area between the separator plate and the GDL, which affects the contact resistance. Since the separator plate and the GDL are objects with different surface roughness, the actual contact area between the two objects in contact has a large effect on the contact resistance. If the contact area between the separator plate and the GDL is large, the contact resistance will be low, and if the contact area is small, the contact resistance will be high, so the effect of reducing the contact resistance will differ depending on how the surface shape of the separator plate is formed.
[0006] The separator plate material is an extremely thin material with a thickness of about tens to hundreds of μm, and the extremely thin material is bright annealed during the manufacturing process. This results in a bright annealed surface with almost no surface irregularities, and if such a material is used as a separator plate as is, there is a problem that the contact area with the GDL is small and the contact resistance is high. Therefore, in order to reduce the contact resistance, it is necessary to make the shape of the separator plate surface uneven to increase the contact area with the GDL, and in this case, it is advantageous for the surface shape to have fine protrusions with a height of tens of nm. Summary of the Invention [Problem to be solved by the invention]
[0007] SUMMARY OF THE PRESENT EMBODIMENT In view of the limitations and problems of the prior art, an object of the present invention is to provide a stainless steel having low contact resistance by forming fine protrusions on the surface thereof as a material for a separator plate for a fuel cell. [Means for solving the problem]
[0008] The metal material for fuel cell separators of the present invention is characterized in that the surface of the metal material in contact with the GDL in the fuel cell has 5 or more fine protrusions of 10 to 100 nm in size, and the ratio of real surface length to apparent surface length without protrusions is 1.15 or more based on a cross-section observed with a transmission electron microscope (TEM).
[0009] The metal material for fuel cell separators of the present invention is preferably a ferritic stainless steel consisting of, by weight, Cr: 15 to 35%, C: 0.02% or less, N: 0.02% or less, Si: 0.4% or less, S: 0.003% or less, Mn: 0.2% or less, Cu: 2% or less, with the balance being Fe and other unavoidable impurities.
[0010] In yet another metal material for a fuel cell separator of the present invention, the metal material is preferably an austenitic stainless steel consisting of, by weight percent, 15-30% Cr, 7-15% Ni, 0.09% or less C, 2.5% or less Si, 0.003% or less S, 3% or less Mn, 3% or less Mo, 0.3% or less N, with the balance being Fe and other unavoidable impurities. Effect of the Invention
[0011] According to the present invention, the method for producing a separator plate of the present invention allows the production of a separator plate having low contact resistance in a fuel cell environment without expensive coating steps. [Brief description of the drawings]
[0012] [Figure 1] This is a transmission electron microscope image of a cross section of a fuel cell separator according to the present invention, which has five or more fine protrusions with a height of 10 to 100 nm or less and whose actual surface length is 15% or more longer than the apparent surface length without the protrusions. [Diagram 2] FIG. 13 is a cross-section of a fuel cell separator plate without protrusions, observed with a transmission electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In one embodiment of the present invention, the metal material for a fuel cell separator has a surface that comes into contact with a GDL in a fuel cell and has 5 or more micro-protrusions of 10 to 100 nm in size, and the ratio of real surface length to apparent surface length without protrusions is 1.15 or more based on a cross section observed with a transmission electron microscope (TEM).
[0014] The surface of bright annealed stainless steel sheet has macroscopic rolling marks that occur in the rolling direction during cold rolling. These rolling marks have a roughness that is too large in scale to be used as a surface shape to increase the contact area between the separator plate material and the GDL, so they do not have a significant effect on the contact resistance. In addition, they cannot be distributed uniformly on the surface, so they do not have a significant effect on the contact area of the entire surface.
[0015] Therefore, by uniformly distributing fine protrusions of 100 nm or less on the surface of the stainless steel, the actual surface area is increased compared to the apparent surface area, and the contact area with the GDL is increased to reduce the contact resistance. If the height of the protrusions is too low, less than 10 nm, the effect on the increase of the surface area due to the protrusions is small, and if the height of the protrusions is too high, more than 100 nm, the number of protrusions per unit area is reduced, so the effect on the increase of the surface area is reduced. If fine protrusions with a height of 10 to 100 nm are uniformly formed on the surface, an actual surface length that is increased by 15% or more compared to the apparent surface length without the protrusions can be formed, which allows the contact area with the GDL to be increased. If the actual surface length is increased by 15% or more in one direction of the surface, the actual contact area increases by 30% or more, and a decrease in contact resistance may occur. In the present invention, fine protrusions with a height of 10 to 100 nm means that there are a large number of protrusions per unit area that are effective in increasing the contact area with the GDL. Therefore, the separator according to the embodiment of the present invention has a contact resistance value of 10 mΩ·cm 2 The present invention is characterized in that:
[0016] Hereinafter, unless otherwise specified, the unit is % by weight. Furthermore, when a part "contains" a certain component, this does not mean that other components are excluded, but that other components may be further contained, unless otherwise specified.
[0017] [Ferritic stainless steel] In one embodiment of the present invention, the metal material for a fuel cell separator is preferably a ferritic stainless steel consisting of, by weight percent, Cr: 15-35%, C: 0.02% or less, N: 0.02% or less, Si: 0.4% or less, S: 0.003% or less, Mn: 0.2% or less, Cu: 2% or less, with the balance being Fe and other unavoidable impurities. Furthermore, according to another embodiment of the present invention, in the metal material for a fuel cell separator, the ferritic stainless steel may further contain at least one element selected from the group consisting of Ti, Nb, and V in a total amount of 1.0% or less.
[0018] C: 0.02% or less It is an austenite forming element and improves high temperature strength when added. However, when added in excess, it reacts with Cr to form chromium carbide, reducing corrosion resistance and reducing elongation and weldability in ferritic steels. Therefore, it is preferable to keep the content as low as possible, 0.02% or less.
[0019] N: 0.02% or less It is an element that stabilizes the austenite phase and has the advantage of improving strength and pitting corrosion resistance as a substitute for Ni, but has the disadvantage of reducing workability such as elongation. Therefore, in the present invention, the content is limited to 0.02% or less.
[0020] Si: 0.4% or less Although it has the advantage of improving high-temperature oxidation resistance and strengthening the passive film in stainless steel to improve corrosion resistance, excessive addition reduces the elongation rate, so the content is limited to 0.4% or less.
[0021] S: 0.003% or less It is a trace impurity element that segregates at grain boundaries and is the main element that causes processing cracks during hot rolling, so its content is limited to as low as possible, 0.003% or less.
[0022] Mn: 0.2% or less Like nitrogen, it is an austenite phase stabilizing element. When added to ferritic steel as a substitute for Ni to metastabilize the austenite phase, it increases strength and reduces workability, so it is limited to 0.2% or less.
[0023] Cu: 2% or less An element that stabilizes the austenite phase and is useful for improving corrosion resistance, but excessive addition can reduce hot workability, so the content should be limited to 2% or less.
[0024] Cr: 15~35% Cr is an element that promotes the formation of oxides in stainless steel. For corrosion resistance, 15% or more Cr must be added. If added in excess, there is a problem that sticking defects increase due to the formation of dense oxide scale during hot rolling, so the Cr content is set at an upper limit of 35%.
[0025] Ti, Nb, V: 1.0% or less in total It is an element effective in forming carbonitrides with the carbon and nitrogen in steel, but since it reduces toughness, the sum of the respective components is limited to 1.0% or less.
[0026] [Austenitic stainless steel] In one embodiment of the present invention, the metal material for a fuel cell separator is preferably an austenitic stainless steel consisting of, by weight percent, Cr: 15-30%, Ni: 7-15%, C: 0.09% or less, Si: 2.5% or less, S: 0.003% or less, Mn: 3% or less, Mo: 3% or less, N: 0.3% or less, with the balance being Fe and other unavoidable impurities. Furthermore, according to another embodiment of the present invention, in the metal material for a fuel cell separator, the austenitic stainless steel may further contain at least one element selected from the group consisting of Ti, Nb, and V in a total amount of 1.0% or less.
[0027] C: 0.09% or less It is an element that stabilizes the austenite phase and is necessary for austenitic stainless steels. When added, it improves high-temperature strength. However, when added in excess, it reacts with Cr to form chromium carbide, reducing corrosion resistance, and also reduces the elongation and weldability of ferritic steels. Therefore, it is preferable to control the content as low as possible, to 0.09% or less.
[0028] N: 0.3% or less It is an element that stabilizes the austenite phase and has the advantage of improving strength and pitting corrosion resistance as a substitute for Ni, but has the disadvantage of reducing workability such as elongation. Therefore, in the present invention, the content is limited to 0.3% or less.
[0029] Si: 2.5% or less An element that improves the corrosion resistance of stainless steel. If contained in excess of 2.5%, it reduces the elongation rate and forms SiO2 oxide inclusions, which reduces the corrosion resistance, so it is limited to 2.5% or less.
[0030] S: 0.003% or less It is a trace impurity element that segregates at grain boundaries and is the main element that causes processing cracks during hot rolling, so its content is limited to as low as possible, 0.003% or less.
[0031] Mn: 3% or less Like nitrogen, it is an austenite phase stabilizing element and an alternative to Ni. However, excessive addition reduces corrosion resistance, so it is limited to 3.0% or less.
[0032] Mo: 3% or less It is an effective element for improving the corrosion resistance of stainless steel. However, if added in excess, it can cause corrosion resistance and brittleness due to the formation of sigma phases. Since it is an expensive element, it is limited to 3% or less.
[0033] Cr: 15~30% It is an element that promotes the formation of oxides in stainless steel and improves corrosion resistance. To ensure corrosion resistance in a fuel cell environment, it must be at least 15%. If it is added in excess, it becomes necessary to further add expensive Ni to stabilize the austenitic phase, Mn which reduces corrosion resistance, and N which reduces workability, so it is limited to 15% to 30%.
[0034] Ni: 7-15% It is an austenite phase stabilizing element and is an expensive element, so its content is limited to 7-15% for economic reasons.
[0035] Ti, Nb, V: 1.0% or less in total It is an element effective in forming carbonitrides with the carbon and nitrogen in steel, but since it reduces toughness, the sum of the respective components is limited to 1.0% or less.
[0036] (manufacturing process) The method for adjusting the surface shape of stainless steel may be carried out through the following steps. The surface shape of the stainless steel may be adjusted by a chemical or mechanical method. When using a chemical method, the surface shape can be adjusted by immersing the stainless steel in an acid solution. The acid solution in which the stainless steel is immersed may be hydrochloric acid, sulfuric acid, nitric acid, or hydrofluoric acid. Two or more of the above acid solutions may be mixed together, or the stainless steel may be immersed in two or more acid solutions sequentially. The surface shape of the stainless steel may also be adjusted by electrolytic treatment, which may include carrying out the electrolytic treatment before and after immersion in the acid solution.
[0037] When using the chemical method, the surface shape may vary depending on the type, temperature, and concentration of the acid solution, the immersion time, and the applied current for the electrolytic treatment. For example, in an acid solution, 5% to 20% sulfuric acid at 40 to 60°C is used, and the current is 0.1 to 0.5 A / cm 2 Alternatively, the wire is immersed in a mixed acid (nitric acid and hydrofluoric acid) at 40°C to 60°C for 30 to 300 seconds, resulting in a surface shape with excellent contact resistance.
[0038] Also, for example, a surface shape with excellent contact resistance can be obtained by immersing the substrate in an acid solution of 5% to 20% hydrochloric acid or 5% to 20% hydrofluoric acid for 30 seconds to 300 seconds. The surface shape of the stainless steel may also be adjusted by mechanical polishing instead of the chemical method. The surface shape will vary depending on the type, thickness, shape and distribution of the abrasives used during polishing. However, the surface shape according to this specification is not limited to the above-mentioned chemical or mechanical methods, but can be derived by various conditions and methods.
[0039] The present invention will now be described in more detail with reference to examples. The following examples are presented to fully convey the concept of the present invention to those skilled in the art to which the present invention pertains, and the present invention is not limited to the examples presented herein and may be embodied in other forms.
[0040] (Example) Table 1 shows the alloy compositions of all the examples including the comparative examples and the inventive examples, which are ferritic and austenitic stainless steels. The stainless steel used in the present invention was prepared by cold rolling stainless steel having the above composition using a Z-mill cold rolling mill in the cold rolling step, and then bright annealing was performed on the cold rolled sheet in the heat treatment step.
[0041] [Table 1]
[0042] Steel A is a ferritic stainless steel according to the present invention, and Steel B is an austenitic stainless steel according to the present invention. In the comparative examples and examples of the present invention, the surface shapes of the ferritic and austenitic stainless steels were adjusted to investigate the relationship between the contact resistance and the surface shape index, and the results are shown in Table 2 below.
[0043] [Table 2]
[0044] Specifically, Table 2 shows the surface analysis results and contact resistance measurements of the cold-rolled steel sheets manufactured, with the average height of protrusions, the number of protrusions between 10 and 100 nm, and the cross section of the steel sheets with actual surface length / apparent surface length measured using a transmission electron microscope (TEM). Surface protrusions effective for contact resistance are very fine with a height of several tens of nm and are difficult to observe with a low-magnification scanning electron microscope (SEM). Therefore, the values in Table 2 were measured using a high-magnification transmission electron microscope of 100,000 times or more, and the average values were obtained by observing 10 locations per specimen. The interfacial contact resistance in Table 2 was evaluated by preparing two sheets of the manufactured material, placing carbon paper (SGL-10BA) used as a gas diffusion layer between them, and applying a contact pressure of 100 N / cm. 2 The interfacial contact resistance at each point was evaluated five times, and the average value was calculated.
[0045] Referring to Table 2, in Examples 1 to 7 having fine protrusions on the surface as defined by the present invention, the contact resistance was 10 mΩ cm 2 The results were excellent below 100 nm. The average height of the protrusions does not have a strong correlation with the contact resistance, but the contact resistance tended to decrease as the number of fine protrusions between 10 and 100 nm increased. There was also a tendency for the actual surface length to be greater compared to the apparent surface length as the number of fine protrusions between 10 and 100 nm increased on the surface. This is thought to have increased the actual contact area with the GDL as a separation plate, thereby reducing the contact resistance.
[0046] However, in Comparative Examples 1 to 9, the number of fine protrusions between 10 and 100 nm, which is the limit of the present invention, is zero or very small, and the contact resistance is less than 10 mΩ cm 2 exceeded. [Industrial Applicability]
[0047] INDUSTRIAL APPLICABILITY The method for producing a separator plate according to the present invention can produce a separator plate having low contact resistance in a fuel cell environment without a costly coating process, and thus the method is industrially applicable.
Claims
1. A metal material for a fuel cell separator, characterized in that the surface of the metal material in contact with the GDL in the fuel cell has 5 or more fine protrusions of 10 to 100 nm in size, and the ratio of real surface length to apparent surface length without protrusions is 1.15 or more based on a cross section observed with a transmission electron microscope (TEM).
2. The metal material for fuel cell separator plates according to claim 1, characterized in that the metal material is a ferritic stainless steel consisting of, by weight percent, Cr: 15 to 35%, C: 0.02% or less, N: 0.02% or less, Si: 0.4% or less, S: 0.003% or less, Mn: 0.2% or less, Cu: 2% or less, the balance being Fe and other unavoidable impurities.
3. 3. The metal material for a fuel cell separator according to claim 2, wherein the ferritic stainless steel further contains at least one element selected from the group consisting of Ti, Nb, and V in a total amount of 1.0% or less.
4. The metal material for fuel cell separator plates according to claim 1, characterized in that the metal material is an austenitic stainless steel consisting of, by weight percentage, Cr: 15-30%, Ni: 7-15%, C: 0.09% or less, Si: 2.5% or less, S: 0.003% or less, Mn: 3% or less, Mo: 3% or less, N: 0.3% or less, with the balance being Fe and other unavoidable impurities.
5. 5. The metal material for a fuel cell separator according to claim 4, wherein the austenitic stainless steel further contains at least one selected from the group consisting of Ti, Nb, and V in a total amount of 1.0% or less.
Citation Information
Patent Citations
Stainless steel for fuel cell separator
KR1020140039326A
Stainless steel for fuel cell separator and method for producing same
WO2018198685A1